PENGARUH TESTIMONI DAN DAYA TARIK INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN : (STUDI PADA LSINTA MUSLIM WEDDING) - Laily Muzdalifah; Hilmiatul Ilmiah (Universitas Nahdlatul Ulama Sidoarjo, 2020)
This study aims to determine the effect of testimonials and the attractiveness of the Instagram on purchasing decisions at Lsinta Muslim Wedding Sidoarjo. This effect test is conducted to determine the effect partially and simultaneously. This research was conducted by using quantitative research. The research sample was 100 respondents. The data source in this study is primary data which is the result of filling out a questionnaire given to consumers who have used the services of Lsinta Muslim Wedding Sidoarjo. The data analysis technique was carried out by testing the hypothesis, namely doing the t test (partial) in addition to the F test (simultaneous). The results of the study show that the testimonial variable has a significant effect on purchasing decisions. For the Instagram attractiveness variable has a significant effect on purchasing decisions. For testing together, it is known that Instagram testimonials and attractiveness significantly influence purchasing decisions.